1989
DOI: 10.1111/apa.1989.78.s361.53
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Infection: The Clinical Evidence

Abstract: Oppenheimer, S. J. (Department of Paediatrics, Universiti Sains Malaysia, Kubang Kerian, Kelantan, Malaysia). Iron and infection: The clinical evidence. Iron deficiency is prevalent in childhood in the developed and developing countries. Programs of presumptive therapy, mass supplementation and food fortification have been introduced in many countries. The unresolved debate over the interaction of iron and infection in the clinical setting prompts re‐evaluation of these practices. Situations of iron overload a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 83 publications
1
21
0
2
Order By: Relevance
“…26 We selected 250 mM as a representation of iron overload that may occur due to hemochromatosis or severe liver disease in humans. 21,27,28 We observed an increased LC3-II to LC3-I ratio after iron treatment, indicating accumulation of autophagosomes (Fig. 1A).…”
Section: Iron Treatment Induces Ferritinophagymentioning
confidence: 81%
See 1 more Smart Citation
“…26 We selected 250 mM as a representation of iron overload that may occur due to hemochromatosis or severe liver disease in humans. 21,27,28 We observed an increased LC3-II to LC3-I ratio after iron treatment, indicating accumulation of autophagosomes (Fig. 1A).…”
Section: Iron Treatment Induces Ferritinophagymentioning
confidence: 81%
“…27,28,54,55 In both of these scenarios, excess free iron is present leading to opportunistic pathogenic burden. A number of case studies have even documented E. coli-associated bacteremia in hemochromatosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is a known trophic factor for several pathogenic bacteria and there has also been concern that iron supplementation of breast-fed infants may saturate human milk lactoferrin, thus diminishing its anti-infective properties (75). Parenteral iron therapy has been associated with the exacerbation of malaria and neonatal sepsis (76). For these reasons, it has been suggested that iron forti cation and supplementation may increase the incidence of gastroenteritis and other infections in infants.…”
Section: Safety Aspectsmentioning
confidence: 99%
“…The availability of iron plays a critical role in host-parasite interactions (13,28,29,41,42). Iron is required for the growth of nearly all forms of bacterial, fungal, protozoal, plant, and animal cells (43,44).…”
mentioning
confidence: 99%